Enzymatic Hydrolysis of Porang by Streptomyces violascens BF 3.10 Mannanase for the Production of Mannooligosaccharides - Azizah Hikma Safitri; Anja Meryandini; Yopi - (Media Peternakan, 2014)
Porang (Amorphophallus muelleri Blume) is an indigenous Indonesian plant containing high hemicellulose as a source of glucomannan. An alternative way to produce a good quality of mannooligosaccharides was through hydrolysis of glucomannan by endo-β mannnase from actynomicetes. Based on 16S rRNA analysis, BF 3.10 isolate, isolated from Bukit Duabelas National Park soil, Jambi was identified as Streptomyces violascens BF 3.10. Reducing sugar was analyzed by dinitrosalicylic acid methods. The highest reducing sugar was achieved at the 72 hours of incubation. Mannanase of isolate BF 3.10 had the highest activity at pH 6 and temperature of 70 °C with enzyme activity of 16.38 U/mL and was stable at 4 °C for 48 h. During 5-hour of hydrolysis with substrate concentration of 0.25%, 0.5%, and 1% porang glucomannan dissolved in 10 mL enzyme, mannooligosaccharides were produced with the degree of polymerization of 2-3. Visualization of the products by using thin layer chromatography (TLC) and high performance liquid chromatography (HPLC) methods showed that mannooligosaccharides produced comprised of glucose, mannobiose, mannotriose, and mannotetraose. The degree of polymerization and the simple sugars produced indicated that mannanase produced by S. violascens actively catalyzed the hydrolysis of 1.4-β-D-mannoside linkage from β-1.4-mannan backbone, that eventually produced simple sugars of mannooligosaccharides.Key words: glucomannan, mannanase, mannooligosaccharides, porang, Streptomyces violascens